Irreducible Dislocation of the Radial Head Associated With Pediatric Monteggia Lesions - Abe, Muneaki (J Am Acad Orthop Surg Glob Res Rev, 2018)
BACKGROUND: In pediatric patients with Monteggia lesions, the radial head can be reduced manually when displacement of the fractured ulna is corrected. Occasionally, however, a dislocated radial head could not be reduced manually even when the length and/or angulation of the fractured ulna had been corrected. We can find such cases in the literature, but those are single case reports. We encountered 17 cases of irreducible dislocation of the radial head in pediatric Monteggia lesions during the past 43 years. The purposes of this study were to identify the characteristics of our cases and to discuss the factors that inhibited reduction of the radial head. METHODS: Of 109 children treated for Monteggia lesions between 1972 and 2015, we encountered 17 cases of irreducible dislocation of the radial head. The patients' ages averaged 7.1 years, ranging from 2.6 to 12.1 years. Directions of the radial head dislocation were anterior in five cases, anteromedial in four, lateral in one, and anterolateral in seven. Most of the patients were referred to us from local orthopaedic clinics because of irreducibility of the radial head. We reduced the radial head surgically and confirmed the causes of irreducibility. RESULTS: In 10 of the 17 cases, the problem was identified as pseudoreduction. In those cases, the radial head was reduced in a supination position but redisplaced in a pronation position. Causes of irreducibility were traced to the annular ligament in 15 cases, biceps tendon in 1, and posterior interosseous nerve in 1. CONCLUSIONS: In cases of pediatric Monteggia lesions, we should pay attention to patients in whom the dislocated radial head is not reduced after closed reduction. The most frequent cause of hindered reduction was interposition of the annular ligament in the radiocapitellar joint. Here, the radial head seems to be reduced in the supination position but becomes redisplaced in the pronation position. After closed reduction, it is important to confirm whether the radial head is stable in both pronation and supination positions. LEVEL OF EVIDENCE: Diagnostic level IV.